Innovative integration of situated and collaborative learning: Enhancing third-grade students’ Chinese reading comprehension and social abilities - Zhao, Xu; Attapaiboon, Tinnakorn; Jantharajit, Nirat (Asian Journal of Contemporary Education, 2025)
This study explores the integration of situated and collaborative learning to enhance third-grade students’ Chinese reading comprehension and social abilities, addressing a critical gap in primary school education research. Situated learning immerses students in realistic contexts while collaborative learning emphasizes teamwork and interaction. The study introduces an innovative pedagogical approach to improve academic and social outcomes by combining these methods. A quasi-experimental design was implemented with two groups of students from a primary school in Shandong, China. The experimental group used the hybrid teaching method while the control group followed traditional instruction. Data collected through reading comprehension tests and social abilities assessments revealed significant improvements in the experimental compared to the control group with large effect sizes in both domains. These findings underscore the combined approach’s effectiveness in fostering deep learning, improving communication skills, and enhancing teamwork. Practical implications highlight the method’s potential to address challenges in traditional teaching by integrating real-world scenarios and collaborative tasks. The study is limited by its short-term focus and sample size, suggesting future research should examine longitudinal effects, broaden participant diversity, and evaluate its impact on other competencies such as writing skills and creativity despite its success. This study contributes to the field by demonstrating a transformative approach to primary education, bridging theoretical learning and practical application.